Pengelolaan Pariwisata Berbasis Komunitas di Sentono Genthong Pacitan Perspektif Maqāṣid Sharī‘ah - Meri Anti Khusnawati; Ely Masykuroh; Amin Wahyudi (Institut Agama Islam Negeri Ponorogo, 2025)
This research is motivated by the phenomenon of community-based management of Sentono Genthong Tourism, which has positively contributed to the transformation of the village from underdeveloped to advanced status, as well as creating employment opportunities in the tourism sector. However, there are emerging dynamics, such as dating activities within the religious tourism area, which raise concerns due to their contradiction with the principle of protecting lineage (ḥifẓ al-nasl) in maqāṣid sharī‘ah. This study is field research using a qualitative approach conducted at Sentono Genthong Tourism in 2023. Data were collected through interviews, observations, and documentation and validated using source, method, and time triangulation. The data analysis was conducted inductively through data reduction, presentation, and conclusion drawing. The findings show that, in general, tourism management has fulfilled the principles of community-based tourism, although there are still shortcomings in the aspect of cross-cultural learning. Seven out of eleven principles of community-based tourism are closely aligned with maqāṣid sharī‘ah, particularly in the elements of protecting religion (ḥifẓ al-dīn), intellect (ḥifẓ al-ʿaql), life (ḥifẓ al-nafs), and wealth (ḥifẓ al-māl). However, the aspect of protecting lineage has not been optimally achieved. In conclusion, while tourism management has been effective and aligns with Sharia principles in several elements, there is a need to strengthen social supervision and visitor education to uphold religious values in this sacred tourism site.